Can a national storage obligation for medicines prevent shortages? Evidence from the Finnish experience - Reko Ravela; Timi Aaltonen; Marja Airaksinen; Alan Lyles (Exploratory Research in Clinical and Social Pharmacy, 2025)
Background: Since 1984, Finland has used storage obligations for essential medicines, requiring manufacturers and importers to maintain storage of certain medicines. This study aimed to investigate whether this type of obligatory storage system for human medicines is effective in preventing and mitigating medicine shortages. Methods: This is a retrospective register study, utilizing open data from Finnish, Norwegian, and Swedish national medicines authorities. We compared the proportion and median durations of shortages between medicines with and without storage obligations within Finland, and the proportion of shortages across Finland, Sweden, and Norway. Results: A total of 1910 shortage notifications met the inclusion criteria for the analysis of shortages within Finland. Medicines not subject to storage obligations experienced between 1.8 and 2.3 times more shortages during the study period compared to those covered by storage obligations. Additionally, the median duration of short-term shortages (lasting less than 21 days) was shorter for medicines that are subject to storage obligations.The inter-country analysis included 1230 shortage notifications from Sweden, 1075 from Norway, and 1369 from Finland. In comparison to Finland, shortages of products equivalent to those subject to storage obligations were 2.5 times more common in Sweden, where no storage obligations are in place, and 2.4 times more common in Norway, where storage obligations are more limited. Conclusions: Our findings suggest that storage obligations for essential human medicines are associated with a lower frequency of shortages. This evidence provides support for other nations considering taking similar policy measures to reduce such shortages.